Interactive Multimedia in Differentiated Learning: Improving Students' Mathematical Representation and Confidence - Kartina, Tina; Sundayana, Rostina; Puspitasari, Nitta (Indonesian Journal of Mathematics Education, 2025)
This study investigates the role of interactive multimedia in differentiated learning to enhance students’ comprehension, mathematical representation, and self-confidence, while accounting for their diverse learning styles. The research involved 97 eighth-grade students at a public junior high school at Garut Regency, Indonesia, divided into four classes. A quantitative approach with a quasi-experimental design was employed, grouping students homogeneously and heterogeneously based on visual, auditory, and kinesthetic learning styles. Data were collected using mathematical comprehension and representation tests, as well as a self-confidence questionnaire. The results show improvements in mathematical comprehension by 17.59 points in homogeneous group and 16.86 points in heterogeneous group, and increases in representation ability by 13.08 and 12.41 points, respectively. Students’ self-confidence also increased in both groups, with a difference of 0.169 points. These findings indicate that interactive multimedia integrated into differentiated learning significantly enhances students’ cognitive and affective outcomes. In conclusion, multimedia aligned with students’ learning styles fosters an inclusive and adaptive learning environment, supports differentiated instruction, and strengthens students’ conceptual understanding and confidence.